Multiple intracranial cryptococcomas in an immunocompetent patient with pulmonary involvement - Sarojini Raman; Nilanjan Mukherjee; Kanakalata Dash; Kamal K Sen (Wolters Kluwer Medknow Publications, 2020)
Opportunistic infections affecting central nervous system (CNS) have high prevalence in developing countries and cryptococcosis is one of them. It is associated with myriad of signs symptoms and clinical behavior. Though commonly associated with AIDS/HIV infection, it has been reported to be pathogenic in immunocompetent patients. Leptomeningitis is most common presentation in CNS, but unusual tumor like mass lesions have been reported. Lungs are primary site of infection, but it can affect different organs with varied clinical presentations. Therefore, correct diagnosis and proper management is essential in such cases excluding the differentials as fatality rate can be quite high. We report such an unusual case of multiple cryptococcal mass lesions in brain in a healthy immune competent individual with bilateral pulmonary involvement.